Antibiotics resistance in pathogenic bacteria isolated from water and sediment around the floating fish farms in the Nha Trang bay - Hanh, Nguyen Kim; Hieu, Nguyen Trinh Duc; Hieu, Nguyen Minh; Thi, Vo Hai; Mien, Pham Thi; Du, Hoang Trung; Thu, Phan Minh; Huan, Nguyen Huu (Vietnam Journal of Marine Science and Technology, 2021)
To assess the impact of antibiotic use in aquaculture in Nha Trang bay, we conducted this study with the aim of assessing antibiotic resistance of opportunistic pathogenic bacteria isolated from water and sediment around shrimp/fish cages in the Nha Trang bay. 109 strains of Vibrio, Salmonella-Shigella and Aeromonas groups were isolated in the surrounding environment of farming areas in Dam Bay and Hon Mieu. Antimicrobial resistance test of these 109 strains showed that in the water environment in Dam Bay, TET (96.6%) and NIT (92.5%) were the two antibiotics with the highest rates of resistant bacteria while no bacteria were resistant to RIF. All 5 types of antibiotics had a statistically insignificant percentage of antibiotic-resistant bacteria in water samples at Hon Mieu, ranging from 33.3% to 68.9%. Also in the water environment, the rate of antibiotic-resistant bacteria in Dam Bay was not influenced by the distance to the cages (42.5–66.6%). Meanwhile, in Hon Mieu, the highest rate of resistant bacteria was observed at the distance of 200 m (100%) away from cages and the lowest rate at the distance of 100 m (20%). In the sediment environment around the cages, both the Dam Bay and Hon Mieu farming areas showed the highest rates of antibiotic-resistant bacteria against TET, NIF and RIF had the lowest rate of resistant bacteria. Among the total of 109 strains tested for antibiotic resistance, 2 strains labeled TCBS_HM200 m and SS_HM200 m were found to be resistant to all 5 tested antibiotics. These two strains were respectively identified as Vibrio harveyi and Oceanimonas sp.